PERBANDINGAN ANTARA JENIS KALIGRAFI KLASIK DAN KALIGRAFI KONTEMPORER - Arum Tri Budi Arti; Nabila Nasfati; Togar Siagian (Jurnal Ekshis, 2024)
Calligraphy is a work of Islamic writing that has something to do with the history of Islamic civilization and the glory of Islam. Besides that, the existence of calligraphy does not only have aesthetic values, but in it there are also noble or spiritual values, which is when a calligrapher makes his written work there is a relationship between him and his rabb, so that is what makes calligraphy have an implied meaning. inside it. The types of division of calligraphy are divided into two, namely types of contemporary calligraphy and classical calligraphy. Therefore the purpose of this research is to find a comparison between contemporary calligraphy and classical calligraphy. This research is qualitative by using literature study using descriptive analysis method. The results of the study show that the comparison between contemporary calligraphy and classical calligraphy is that, if the type of contemporary calligraphy contains a lot of aesthetic or aesthetic values, contemporary calligraphy deviates a lot from the basic calligraphy formula. Whereas in the type of classical calligraphy, that is, it follows the rules of the procedure for writing according to the basic calligraphy formula. It focuses more on writing procedures according to the basic formula of calligraphy without containing aesthetic values